BLOOD SERUM CYTOKINE PROFILE IN PATIENTS WITH СRONIC EXTENDED DERMATOSES AND ENDOGENOUS INTOXICATION SYNDROME - T. V. Kopytova; N. A. Dobrotyna; L. N. Himkina; N. A. Shelchkova; G. A. Panteleeva (Медицинская иммунология, 2014)
Abstract. The article presents data about blood serum cytokine profile in patients with chronic widespread dermatoses, associated with increase in blood markers of endogenous intoxication (EI) syndrome, i.e., lowand medium-molecular mass substances (LMWS). A close interrelation has been revealed between EI levels, and cytokine profiles. In the patients with high amounts of blood LMWS, increased levels of anti-inflammatory IL have been shown. Correlation analysis of clinical and laboratory parameters has demonstrated a leading role of EI in pathogenetic mechanisms of chronic extended dermatoses, and brings about altered regulation of metabolic processes. A severe clinical course of dermatoses (i.e., therapy resistance) was associated with a  considerable  decrease  in  blood  IL-8  and  IL-10  levels,  along  with  high  IgE  and  LMWS  amounts. (Med. Immunol., 2011, vol. 13, N 2-3, pp 205-210)